Committee on High‐quality Alzheimer's Disease Studies (CHADS) consensus report. Issue 6 (29th September 2021) - Jicha, Greg A.; Abner, Erin L.; Arnold, Steven E.; Carrillo, Maria C.; Dodge, Hiroko H.; Edland, Steven D.; Fargo, Keith N.; Feldman, Howard H.; Goldstein, Larry B.; Hendrix, James; Peters, Ruth; Robillard, Julie M.; et al.
Abstract: Background: Consensus guidance for the development and identification of high‐quality Alzheimer's disease clinical trials is needed for protocol development and conduct of clinical trials. Methods: An ad hoc consensus committee was convened in conjunction with the Alzheimer's Association to develop consensus recommendations. Results: Consensus was readily reached for the need to provide scientific justification, registration of trials, institutional review board oversight, conflict of interest disclosure, funding source disclosure, defined trial population, recruitment resources, definition of the intervention, specification of trial duration, appropriate payment for participant engagement, risk‐benefit disclosure as part of the consent process, and the requirement to disseminate and/or publish trial results even if the study is negative. Conclusions: This consensus guidance should prove useful for the protocol development and conduct of clinical trials, and may further provide a platform for the development of education materials that may help guide appropriate clinical trial participation decisions for potential trial participants and the general public.